THE EFFECT OF ORGANIZATIONAL CULTURE, LEADERSHIP STYLE, KNOWLEDGE MANAGEMENT, WORK DISCIPLINE, AND WORK ENVIRONMENT ON EMPLOYEE SATISFACTION PBEC EYE HOSPITAL - Agus Taufiq; Isyandi Isyandi; Yusni Maulida (JURNAL MANAJEMEN DAN BISNIS, 2021)
This study aims to analyze the influence of organizational culture, leadership style, knowledge management, work discipline, and work environment on job satisfaction of employees of Pekanbaru Eye Center Eye Center. The data of this study consisted of primary and secondary data, which were taken through a questionnaire to 81 employees of the Pekanbaru Eye Center Eye Center with a sample census. The variables used are organizational culture, leadership style, knowledge management, work discipline and work environment as independent variables and job satisfaction as the dependent variable. The data obtained were processed using SmartPLS. The results of this study indicate that organizational culture, leadership style and work environment have a positive and significant effect on employee job satisfaction. Knowledge management has a negative effect on employee job satisfaction, and work discipline does not have a significant effect on employee job satisfaction.